Peran influencer keagamaan (Da’i Digital) dalam membentuk opini publik: Moderasi beragama di media sosial - Suherman, Sunandar (Maliki Interdisciplinary Journal, 2025)
This study aims to analyze the role of religious influencers (digital preachers) in shaping public opinion on religious moderation through the Instagram platform. The phenomenon of increasing digital preaching activities and consumption of religious content by the younger generation has made Instagram a strategic space for the dissemination of religious discourse. The research method used a descriptive qualitative approach through content analysis of religious influencers’ posts and observation of audience interactions in the comments section. The results show that digital da’i have a significant influence in framing the narrative of religious moderation through visual communication strategies, storytelling, and the selection of issues relevant to everyday life. Positive interactions from followers indicate the formation of a more inclusive, tolerant, and moderate public opinion. This study confirms that the presence of religious influencers on social media not only serves as a conveyor of religious messages but also as actors who shape a more adaptive discourse on diversity in the digital space.